Assessment on Energy Technology Toward Carbon Neutrality Policy Using Multi-Criteria Decision Analysis: A Case of Thailand - Wangjiraniran, Weerin; Pongthanaisawan, Jakapong; Nakapreech, Nitida (International Journal of Energy Economics and Policy, 2023)
The assessment of greenhouse gas (GHG) mitigation technologies creates a knowledge database to support a national strategy to meet Thailand’s GHG emission reduction target. Such a database also makes important contributions to the formulation of research policy and the country’s broader technological development. Thailand needs a strong technological base in order to meet its national policy targets and international obligations for reducing GHG emissions, as well as to reduce the negative effects of economic activity on society and the environment and to create additional value. The goal of this study is to prioritize energy technologies so that Thailand can achieve its carbon neutrality goal by the year 2050. Multi-criteria decision making is applied with quantitative data on GHG mitigation options. Decisions are made based on the technology’s readiness and level of its impact on economic, social and environmental development. Critical issues representing needs and barriers for selected key technologies are analyzed. The results indicate that solar energy and electric vehicle are selected as having the highest priority, followed by energy efficiency and other renewable energy sources. Carbon capture, utilization and storage (CCUS), green hydrogen, and carbon sinks are the last choices with high uncertainty about commercialization.